Aging and structural change - Ulrich Thießen (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
Many studies analyzed in depth how aging affects aggregate economic performance. But analyses of these effects on the employment structure are scarce and they do not consider that consumption patterns, the supply of goods and services, and also sectoral labor productivity are all likely to adjust to aging and will change. Hence, regression analysis of sectoral employment shares is proposed that controls for aging. For a large panel of countries and a long time period it is found that aging indeed affects relative employment of most sectors statistically highly significant either positive or negative. We also conclude that aging tends to accelerate ongoing structural change. This enables to derive specific policy implications. The approach could thus become a new method in forecasting employment and other effects of aging.
Keywords: J11; O57; C33; 330; Aging; Structural Change; Panel Regressions; Alternde Bevölkerung; Strukturwandel; Sektorale Beschäftigungsstruktur; Panel; Welt